The Magic Finger - Dahl, Roald; Illustrated by Blake, Quentin (London Puffin Books, 2013)
The Gregg family loves hunting, but their eight-year-old neighbor can't stand it. After countless pleas for them to stop are ignored, she has no other choice--she has to put her magic finger on them. Illustrations.
Include Illustration
Keywords: Hunting stories -- Anger